New evidence on the psychometric properties of the Portuguese version of the Flourishing Scale - Rando, Belén (2022)
This research aims to bring new evidence concerning the psychometric properties of the Portuguese version of the Flourishing Scale (FS-P) in a sample of the general Portuguese population. Participants consisted of 396 Portuguese adults between 18 and 52 years of age. We collected data mainly via an online survey following a snowball sampling strategy. We analyzed FS-P validity evidence based on its internal structure, measurement invariance across gender, reliability of test scores, homogeneity indices of the items, and validity evidence based on association with measures on life satisfaction (single-item), self-esteem (RSES), self-control (SCBS), loneliness (DJGLS), depression (CES-D 10), and distress (K6+). Confirmatory factor analysis showed a one-factor solution. Configural, metric, and scalar invariance across gender was tenable with adequate fit indices. The reliability analysis showed adequate internal consistency (McDonald’s Omega = 0.88) and adequate homogeneity indices for all items. We obtained positive correlations between FS-P scores and measures on life satisfaction, self-esteem, and self-control, and negative correlations with scores on loneliness, depression, and distress (significance level of 0.05). All correlations values were close to |0.50|. These results sustain the importance of such a practical short scale in research and clinical contexts.